Struggle, Perseverance, and Parental Love in The Pursuit of Happyness (2006): A Dramatic Analysis of Character Development and Conflict - Natalia Kolis; Noseni Petrus M. Kalawen (TEKILA: Journal of Language Teaching and Literature, 2024)
This study analyzes the film The Pursuit of Happyness (2006), directed by Gabriele Muccino and based on the autobiographical story of Chris Gardner. The purpose of this study is to examine the character development, narrative conflict, and thematic messages presented in the film. The research applies a qualitative descriptive approach using narrative analysis to interpret the characters, events, dialogues, and visual elements portrayed in the story. The findings show that the film centers on the struggle of Chris Gardner, a single father who faces severe financial hardship while trying to provide a better life for his son. Throughout the narrative, Chris demonstrates perseverance, determination, and strong parental responsibility despite experiencing unemployment, homelessness, and social pressure. The conflict of the story develops through Chris’s efforts to balance his responsibilities as a father while pursuing an unpaid internship at a brokerage firm in hopes of achieving financial stability. The study also identifies several important themes, including perseverance, parental love, self-confidence, and the struggle against poverty. These themes are reflected through key scenes and dialogues that emphasize the importance of hard work, optimism, and belief in one’s potential. In addition, symbolic elements such as the public restroom, the apartment key, and the basketball represent hardship, opportunity, and personal dreams. The analysis indicates that The Pursuit of Happyness not only presents an inspiring story of personal success but also conveys moral values related to resilience, responsibility, and hope in overcoming life’s difficulties.